Piero Calamandrei et la Constitution de 1948 : Calamandrei le juriste contre Piero l’intellectuel - Frédéric Attal (Laboratoire Italien)
Piero Calamandrei was a well-known legal-adviser and an intellectual engagé. He founded and directed a political and cultural monthly magazine, still alive, Il Ponte, which was committed in the Fifties in the rank of the non-communist, non Marxist and neutralist Left wing. He was also a most competent member of the Committee of 75 in charge of writing the Constitution. This paper studies how Calamandrei stood for a presidential system, inspired of the American Constitution, while most of his political friends, from the Socialist and the Communist Parties supported a traditional parliamentary Constitution. If the intellectual was more and more attracted by the Radicals, the constitutional lawyer remained linked to a very classical and orthodox conception of liberalism.